Notes on the avifauna of Bacan, Kasiruta and Obi, North Moluccas - Lambert, Frank R (KUKILA, 1994)
In 1991 and 1992, field work was conducted in the north Moluccas under the he auspices of IUCN (the World Conservation Union) to ascertain the status of three species of parrot: White Cockatoo Cacatua alba, Chattering Lory Lorius garrulus and two subspecies of Violet-backed Lory Eos squamata riciniata and E. s. obiensis (Lambert 1993; in press). During these survey, about one month was spent on Bacan October/November 1991), four day on the adjacent island of Kasiruta (November 1991) and a further month on Obi (February 1992). Most of the parrot surveys were conducted in the lowlands and hills, although observations were made up to 1,300 m on the steep forested western slopes of Mt Sibela, Bacan, and at altitudes of up ca. 730 m in the upper catchment of the Widi Besar River, Obi. Even at these higher altitudes, however, the forest was tall, with trees estimated to be 30-35 m tall, and best described as submontane rather than montane even at 1,300 m. Unfortunately, it was not possible to reach the true montane forests of Mt Sibela (maximum elevation 2111m).